The street lawyer : a novel - Grisham, John. (New York : Dell, 2010)
After a violent encounter with a homeless man, talented corporate lawyer Michael finds himself out in the streets, lucky to be alive, and holding a top-secret file belonging to his former employers.
Originally published: New York : Doubleday, c1998.
Keywords: Washington (D.C.) -- Fiction; Washington (D.C.); Washington (D.C.) -- Fiction; Legal fiction (Literature); Legal stories; Fiction; Legal stories; Legal fiction (Literature); Legal stories